CAPILLARIA HEPATICA (NEMATODE) IN RODENTS OF THE LAHORE METROPOLIS CORPORATION – PAKISTAN - M. S. Ahmad; A. Maqbool M. Mahmood-ul-Hassan; M. Mushtaq-ul-Hassan; A. A. Anjum (Journal of Animal and Plant Sciences, 2011)
A total of 3600 rodents were live-trapped from three different localities (1200 each) of the Lahore Metropolitans Allama Iqbal Town, Walled City and Railway Station and adjacent areas, and scanned for the prevalence of Capillaria hepatica. In each of these four types of structures were sampled for rats and mice namely residential houses (RH), flour mills (FM), fruit/vegetable shops (F/VS) and departmental stores/grocery shops (DS/GS). Majority of the trapped rodents included house rats Rattus rattus (n = 3190) with a few house mice Mus musculus (n = 410). Hepatic capillariasis was recorded in 7.0% of the rodents in Lahore city. The prevalence was statistically higher in females than in males and in adults than young animals. A significant difference was found in the infection rate between rats and mice. Similarly the infection rate varied significantly both monthly and seasonally and the peak prevalence was recorded during summer (10.8%). Inter-structure infection rate was non-significant.
Keywords: C. hepatica; R. rattus; M. Musculus; Rodents; Hepatic Capillariasis.